Impact of Metaverse Technologies Integration on Biotechno-logical Innovation: A Literature Review - Feta, Amra Abazi; Kamberaj, Hiqmet (European Scientific Journal, ESJ, 2025)
The convergence of metaverse technologies (such as virtual reality, augmented reality, artificial intelli-gence, and digital twins) into biotechnology is ushering in a new age for the creation of pharmaceuticals, medical science research, and teaching. The interactive and immersive environments enable collaboration without geographical limitations through virtual labs, improve the articulation of complex biological processes, and accelerate experiments using enhanced models powered by artificial intelligence. High-visibility use cases comprise virtual clinical trials founded on digital twin models that simulate individual patient profiles. The application of AI in drug discovery medicine, with its expedited time-to-market and 3D learning environments, enhances the knowledge and procedural precision of biotech professionals. This study employs a qualitative methodological approach, comprising an extensive literature review coupled with a case study analysis, to reflect on the participation of metaverse technologies within the biotechnology sector. This systematic review focuses on the transformative role of the metaverse in biotechnolo-gy, analysing its capacity to enable global collaboration, advanced simulations, and immer-sive education. By synthesising peer-reviewed literature (2019-2025), we highlight key ad-vancements, such as AI-driven drug discovery and virtual laboratories, while addressing critical challenges, including data privacy, ethical concerns, and computational require-ments. In this review, we aim to highlight the metaverse’s potential to transform biotechno-logical research and emphasise the need for interdisciplinary solutions to harness its bene-fits. Drawing on an analysis of trends in cloud collaboration, digital simulation, immersive learning, and ethical issues, the research provides a critical analysis of the challenges and problems posed by the digital revolution. Key areas discussed in immense detail include data privacy, algorithm bias, computational infrastructure, and regulatory uncertainty. Our findings emphasise the need for interdisciplinary research and the provision of comprehensive ethi-cal and technical guidelines to enable the secure and equitable use of metaverse technologies in biotech-nology. This study will primarily contribute to the growing corpus of scholarly literature by providing a concise and logical synthesis of existing knowledge, identifying key areas for future research and devel-opment.